Francois, Gilbert Viault - Gilbert Viault, Francois (1957)
During a memorial plaque have been placed to Professor FG Viault in the laboratories of the Institute of Andean Biology in Morococha, we wanted to play as a tribute to the wise investigator submissions to the Academy of Sciences in Paris, 1890 and 1891, which gives account of his findings on hematology altitude.